Pais estimator for the reliability function of the Pareto model of Type I failure - هادي صباح; صالح ستار محمد (Journal of Economics and Administrative Sciences, 2010)
In this paper an estimator of reliability function for the pareto dist. Of the first kind has been derived and then a simulation approach by Monte-Calro method was made to compare the Bayers estimator of reliability function and the maximum likelihood estimator for this function. It has been found that the Bayes. estimator was better than maximum likelihood estimator for all sample sizes using Integral mean square error(IMSE).